Coercion, capacity, and coordination: Predictors of political violence. (July 2013) - Bell, Sam R; Cingranelli, David; Murdie, Amanda; Caglayan, Alper
Using a risk assessment method developed by Gurr and Moore ( American Journal of Political Science 41: 1079–1103, 1997) and applying O'Brien's ( Journal of Conflict Resolution 46: 791–811, 2002) risk assessment metrics, we present a global, comparative, cross-national model predicting the states where political violence is likely to increase. Our model predicts more political violence when governments violate the physical integrity rights of their citizens—especially when they frequently imprison citizens for political reasons or make them "disappear". These coercive techniques may create more citizen dissatisfaction than other types of violations of physical integrity rights, because citizens perceive political imprisonment and disappearances as the direct result of the deliberate policy choices of politicians. Our model also forecasts more political violence in weak states and states that allow dissatisfied citizens to coordinate their anti-government activities. Specifically, we demonstrate that political violence tends to be higher if governments respect their citizens' right to freedom of assembly and association and offer widespread use of mobile phone and internet technology.